Leadership turnover among university presidents - Heinke Röbken (Management Revue, 2007)
This study examines leadership succession among university presidents. Strategy researchers have emphasized that changing leaders is an important organizational decision which is likely to affect the strategic direction of the organization (e.g. Hambrick/Fukutomi 1991). Using longitudinal data on German university presidents and rectors, three issues are addressed: (1) Presidential tenure is related to selected organizational features. One characteristic to which particular importance is attributed in the succession literature is organizational size. This study analyzes on an organizational level how the office tenure of current university presidents and rectors relates to university size. (2) On the level of the overall university system, a longitudinal study is conducted in order to determine how the average tenure of German university presidents changed between 1960 and 2000. Five different methods for measuring presidential tenure are developed and compared. The results indicate a decrease in presidential tenure since the early 1990s. (3) In order to analyze potential determinants of the decreasing time in office, correlation analyses are conducted. The results suggest that public funding for teaching and increasing pressures for reforms are significantly related to presidential time in office. Resource endowments for research are not related to presidential tenure. Finally, the implications of the decreasing office tenure for managing organizational change in universities are discussed.
Keywords: 650; leadership Turnover; succession; presidential Tenure; university presidents; organizational change